LA PRATIQUE DU DÉVELOPPEMENT DURABLE PAR LES TRANSPORTEURS ROUTIERS MAROCAINS (CAS DE LA VILLE DE TANGER. MAROC) ETAT DES LIEUX, IMPACTS SUR L’ENVIRONNEMENT ET RECOMMANDATIONS - Jihad Jami; Said Kammas (European Scientific Journal, ESJ, 2013)
Sustainable development has become fashion in such way that sometimes it is rendered meaningless. Sustainable transport is the expression of sustainable development in the transport sector.Mobility of people and goods has undergone a rapid economic and social growth through the recent years. However, the progress achieved thanks to mobility may become harmful and is likely to to be a serious obstacle to countries which opted for sustainable development policy.Transport, being the heart of economy, is one of the most energy consumming sector. The increase of traffic and mobility has certainly beneficial effects, but it also has a negative impact on resources as well as a higher energy cost.To deal with the issue of sustainable transport in a region with a very high transit flow is not an easy matter. We will try, throughout this work, to study this matter and put forward a few ideas in response to the problem thanks to a regional investigation on the application of sustainable development by haulage.